Assessing Subjective and Clinical Response to Flunisolide and Saline Nasal Irrigation In Patients With Allergic Rhinitis - Zafar, Anoosha; Manzoor, Faisal; Riaz, Naeem; Shaheen, Fariha; Shaukat, Shahzaib; Kalsoom, Rahat (Pakistan Armed Forces Medical Journal, 2026)
Objective: To assess subjective and clinical response to flunisolide and saline irrigation in patients with allergic rhinitis.Study Design: Quasi-experimental study.Place and Duration of Study: Combined Military Hospital (CMH), Rawalpindi, Pakistan, from Feb 2023 to Jan 2024.Methodology: With consecutive sampling technique, 116 participants were included in the study. Those patients who were prescribed flunisolide nasal spray were labeled as the “exposed group” whereas patients receiving normal saline irrigation constituted the “unexposed/ control group”. After 3 months, every patient had a thorough evaluation which included an endoscopic nasal examination, and a review of Sinonasal Outcome Test-22 (SNOT-22) questionnaire.Results: Study included 81(69.80%) males and 35(30.20%) females. Mean age of the participants was 33.18±7.96 years. The change in median SNOT score after treatment was 37 in exposed group as compared to 14 in unexposed group which was statistically significant (p < 0.001). Individually, 16 out of 22 symptoms checked by SNOT questionnaire (all except dizziness, ear pain, facial pain, difficulty falling asleep, lack of good night sleep and fatigue) showed statistically significant improvement (p < 0.001) when flunisolide nasal spray was used instead of saline nasal irrigation.Conclusion: Flunisolide is more effective in controlling symptoms of allergic rhinitis (AR) as compared to normal saline after a period of 3 months. These findings allow the therapy of allergic rhinitis to be tailored depending upon the specific symptoms of each patient.